2011
DOI: 10.1038/jes.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to organochlorine pesticides is an independent risk factor of hepatocellular carcinoma: A case–control study

Abstract: Primary hepatocellular carcinoma (HCC) is highly prevalent in China. Although hepatitis B virus (HBV) and aflatoxin B1 (AFB1) are considered the major risk factors, among the high-risk cohorts only a small fraction develops liver cancer. Therefore, we investigated whether organochlorine pesticide exposure contributed to HCC risk in the Xiamen population. The questionnaire database was built from 346 HCC cases and 961 healthy controls during [2007][2008][2009]. The serum levels of a-, b-, g-, d-HCH, 1,1,1-trich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…1) and after exclusions, 48 full-text papers were assessed for eligibility. After the exclusions described above, 15 studies were included in the review (Table 1) [40–54]. Most studies were conducted in China (n=4) and Egypt (n=4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and after exclusions, 48 full-text papers were assessed for eligibility. After the exclusions described above, 15 studies were included in the review (Table 1) [40–54]. Most studies were conducted in China (n=4) and Egypt (n=4).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported a statistically significant protective effect of employment in the agriculture industry, although there was no adjustment for major risk factors [44]. The strongest evidence for an association was observed among three biomarker-based studies (two of which were prospectively assessed) conducted in China directly measuring organochlorine pesticides in serum and demonstrating statistically significant linear trends with increasing DDT levels and increasing HCC risk [48, 49, 54]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of important cofactors, such as HBV, HCV and AFB1, amplifies the risk in exposed populations [152][153][154][155][156][157][158] .…”
Section: Pesticidesmentioning
confidence: 99%
“…hepatocellular carcinoma (Zhao et al, 2011), breast cancer (Salehi et al, 2008), cancer of the head and neck (Govett et al, 2011), non-Hodgkin lymphoma (Engel et al, 2007), prostate cancer (Xu et al, 2010), testicular germ cell tumors (McGlynn et al, 2008), or pancreatic cancer (Hardell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%